A worldwide bibliometric analysis on euthanasia - Özden Güdük (SERNEV, 2024)
Introduction: Euthanasia, which allows individuals with an incurable disease to end their lives in an honourable way, is a long-debated practice. It is related to various issues such as culture, philosophy, religion, ethics, public value, and efficient use of health resources. While some advocate for the right of individuals to choose euthanasia, others criticize it on ethical, legal, and religious grounds. Methods: In this study bibliometric analysis was used and the data were obtained from the Web of Science Core Collection database on July 26, 2024. Only English publications and articles were included using keywords such as "euthanasia," "end-of-life decisions," "medical assistance in dying," "physician-assisted death," and "physician-assisted suicide" without time restrictions. VOSviewer software was used to create network and density graphs, and SciMAT software was used to create strategic diagrams.Results: A total of 2,230 studies published between 1980 and 2024 were analyzed. The author with the most publications is Deliens, L, with 86 studies. The majority of studies were published in the USA, Netherlands, and Canada (692, 336, 225 respectively). The most frequently used keywords are euthanasia, palliative care, and ethics. The highest number of publications (149) was in the year 2021. In the strategic diagram for the first period (between 1980 and 2001), the themes of care and ethics were prominent, while for the second period (between 2002 and 2024), the clusters of nurse and shared decision-making were notable. Conclusion: After its legalization in the Netherlands, euthanasia has been accepted and implemented in some countries over the years, with variations in scope. Some countries, like the Netherlands and Belgium, also accept health problems related to old age and mental illness as euthanasia requests. The discussion around euthanasia often revolves around the principles of medical ethics, including autonomy, beneficence, non-maleficence, and justice. Studies have focused on the role of physicians and nurses in the process, as well as end-of-life decision-making by patients. Recently, Canada defined the role of nurses in the euthanasia process, marking a significant development.